Connection is the weakest point of the structural building system. Structural construction building system must ensure that there is only a tensile force or just axial compression that is working on the connection. Data on the lateral design values (Z) double shear connection wood beam with nails of steel side plates for various types of tropical Indonesian wood have not studied much. Average moisture content (MC) for the main member varies from 13.3 to 22.5% while average specific gravity (r) f - Sucahyo SADIYO; Naresworo NUGROHO; Surjono SURJOKUSUMO; Imam WAHYUDI (Departemen Hasil Hutan, IPB, 2012)
Connection is the weakest point of the structural building system. Structural construction building system must ensure that there is only a tensile force or just axial compression that is working on the connection. Data on the lateral design values (Z) double shear connection wood beam with nails of steel side plates for various types of tropical Indonesian wood have not studied much. Average moisture content (MC) for the main member varies from 13.3 to 22.5% while average specific gravity (r) from 0.27 to 0.76 and then wood density from 0.31 to 0.89 g/cm3. From this average value of MC, SG and wood density the lowest is sengon and the highest is rasamala wood. Average allowable load of compression parallel to grain ( ) and parallel tensile ( )is sengon, but the highest is bangkirai. There is a general tendency that and is linier to r of those wood. is approximately 2 times greater than its . The number of nail (4-10 pieces) did not give effect of average Z, but with the nail diameter 4.1 to 5.2 mm Z increased significantly and this value decreased on 5.5 mm diameter nail. Average Z also increases with increasing of ρ for displacement 1.50 mm (Indonesian Standard PKKI NI-5 1961)) and 5.0 mm (breaking load). The increasing of Z happens because ρ effect. At 5.0 mm displacement the increase of Z is not as sharp as that of 1.5 mm. Power regression type is the best equation to predict Z of wood density for several diameters of nails. Keywords : Allowable load of tensile parallel to grain, density, displacement, double shear connection, lateral design values